2014
DOI: 10.1111/lam.12366
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fosA5 , a new plasmid-mediated fosfomycin resistance gene in Escherichia coli

Abstract: This study aimed to clone and characterize a plasmid-mediated fosA subtype gene, fosA5, in a clinical strain of ESBL-producing Escherichia coli, which confers fosfomycin resistance. Detection of the fosA5 gene clarified the mechanism of fosfomycin resistance in a strain that was negative for known fosfomycin resistance genes. Monitoring and surveillance will be important to follow the changes in fosfomycin resistance and prevent further dissemination of fos genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…fosA is frequently identified in the E. coli and K. pneumoniae genomes 35,36 . The fosA5 gene is first found in E. coli in 2014 37 . In 2017, it was reported that all of 73 carbapenem-resistant K. pneumoniae isolates were positive for fosA5 in one Chinese area: Zhejiang Province 38 .…”
Section: Discussionmentioning
confidence: 99%
“…fosA is frequently identified in the E. coli and K. pneumoniae genomes 35,36 . The fosA5 gene is first found in E. coli in 2014 37 . In 2017, it was reported that all of 73 carbapenem-resistant K. pneumoniae isolates were positive for fosA5 in one Chinese area: Zhejiang Province 38 .…”
Section: Discussionmentioning
confidence: 99%
“…It catalyzes the reaction between glutathione and fosfomycin to an inactive adduct (102,(105)(106)(107). New subtypes, with similar structure, of the gene have been described (fosA2, fosA3, fosA4, and fosA5) (108)(109)(110). Cooccurrence in plasmids with bla CTX-M , bla NDM , bla KPC , bla OXA , bla CMY , bla AmpC , bla TEM , bla SHV , bla SFO-1 , gyrA, parC, parE, sul1, sul2, strA, strB, aac(6=)-Ib, aadA5, aphA6, tetA(A), mphA, floR, dfrA7, rmtB, and merA genes has been reported, conferring resistance to ␤-lactams, quinolones, aminoglycosides, macrolides, sulfonamides, and tetracyclines (75,80,(111)(112)(113)(114).…”
Section: Acquired Resistancementioning
confidence: 99%
“…By far the most widespread plasmid-borne fosA is fosA3, which has been reported to be present in up to 90% of fosfomycin-resistant extended-spectrum-␤-lactamase (ESBL)-producing E. coli isolates in China (8). Chromosomally encoded fosA from K. pneumoniae (fosA KP ) also represents a substantial risk to human health because it confers intrinsic reduced fosfomycin susceptibility in K. pneumoniae and can also serve as a reservoir for the nearly identical plasmid-borne genes fosA5 and fosA6 (9,10).…”
mentioning
confidence: 99%